Long-term Urinary Catheter Users Self-Care Practices and Problems - Wilde, Mary (2013)
AIMS: The aims were to characterize a sample of 202 adult community-living long-term indwelling urinary catheter users, to describe self-care practices and catheter problems, and to explore relationships among demographics, catheter practices, and problems. BACKGROUND: Long-term urinary catheter users have not been well studied, and persons using the device indefinitely for persistent urinary retention are likely to have different patterns of catheter practices and problems. DESIGN: The study was a cross-sectional descriptive and exploratory analysis. METHODS: Home interviews were conducted with catheter users who provided information by self-reported recall over the previous two months. Data were analyzed by descriptive statistics and tests of association between demographics, catheter practices, and catheter problems. RESULTS: The sample was widely diverse in age (19–96 years), race, and medical diagnosis. Urethral catheters were used slightly more often (56%) than suprapubic (44%), for a mean of 6 yrs. (SD 7 yrs.). Many persons were highly disabled, with 60% having difficulty in bathing, dressing, toileting, and getting out of the bed; 19% also required assistance in eating. A high percentage of catheter problems were reported with: 43% experiencing leakage (bypassing of urine), 31% having had a urinary tract infection, 24% blockage of the catheter, 23% catheter-associated pain, and 12% accidental dislodgment of the catheter. Treatments of catheter-related problems contributed to additional health care utilization including extra nurse or clinic visits, trips to the emergency department, or hospitalization. Symptoms of catheter associated urinary tract infections were most often related to changes in the color or character of urine or generalized symptoms. CONCLUSIONS: Catheter related problems contribute to excess morbidity and health care utilization and costs. RELEVANCE TO CLINICAL PRACTICE: More research is needed in how to minimize catheter associated problems in long-term catheter users. Information from this study could help inform the development of interventions in this population.